The foreign policy of counter secession : preventing the recognition of contested states - Ker-Lindsay, James, 1972- (Oxford : Oxford University Press, 2012)
How do states prevent the recognition of territories that have unilaterally declared independence? At a time when the issue of secession is becoming increasingly significant on the world stage, this book considers this crucial question.
Includes bibliographical references and index.
Description based on print version record.
Keywords: International relations; World politics; Secession; Separatist movements